2016
DOI: 10.1186/s12955-016-0545-0
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the Chinese mandarin version of PedsQL™ 3.0 transplant module

Abstract: BackgroundLong-term health-related quality of life (HRQoL) of pediatric patients after hematopoietic stem cell transplantation (HSCT) is increasingly studied worldwide. However, few studies have been performed in China, where no uniform scale is available; the PedsQL™ Cancer Module 3.0 Chinese Mandarin version has been used to evaluate HRQoL of patients after HSCT in China. This study aimed to assess the reliability and validity of the Chinese Mandarin version of PedsQL™ 3.0 Transplant Module.MethodsPatients b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
(17 reference statements)
2
6
0
1
Order By: Relevance
“…Additionally, we found that most of the missed items were about “School functioning”, indicating that children after HSCT recover slowly due to their weaker immunity and higher susceptibility to infection. This finding is comparable to that reported in the previous study ( 18 , 20 , 27 ). Not only the patients after HSCT, but the children with cancer after chemotherapy may miss school life due to clinic visits, hospitalizations, or intercurrent illnesses, which may explain why the children with HSCT reported a lower HRQoL than healthy children, especially in “School functioning”.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, we found that most of the missed items were about “School functioning”, indicating that children after HSCT recover slowly due to their weaker immunity and higher susceptibility to infection. This finding is comparable to that reported in the previous study ( 18 , 20 , 27 ). Not only the patients after HSCT, but the children with cancer after chemotherapy may miss school life due to clinic visits, hospitalizations, or intercurrent illnesses, which may explain why the children with HSCT reported a lower HRQoL than healthy children, especially in “School functioning”.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding aim 1, step-wise multiple linear regression was conducted to investigate the statistically significant predictors associated with global QOL. Regarding aim 2, the Spearman rank correlation coefficients between QLQ-C30 and QLQ-BR23 subscales were firstly calculated, with correlation coefficient > 0.5 indicating a moderate association and a value < 0.5 representing a weak association [ 23 ]. Next, the latent factor structure was explored by using an exploratory factor analysis (EFA).…”
Section: Methodsmentioning
confidence: 99%
“…However, rare conditions pose challenges to the translation of a HRQOL questionnaire, why the standard procedure may need practical adaptation, such as producing less forward-backward translations [ 35 , 36 ]. Moreover, many HRQOL measures have been developed in English [ 35 ], and have been translated from English into Chinese [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. The EA-QOL questionnaires were developed in the Swedish language, and Sweden is a low-population country.…”
Section: Discussionmentioning
confidence: 99%
“…Then, studies have demonstrated overall acceptable psychometric performance of the EA-QOL questionnaires among children with EA in Turkey, Poland and the Netherlands [ 20 , 21 , 22 ]. Many QOL/HRQOL questionnaires have been translated from English to Chinese, and the Chinese version of the questionnaires has achieved satisfactory validity and reliability [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. In order to increase knowledge of HRQOL of children with EA in China, it is central to investigate the psychometric properties of the EA-QOL questionnaires among Chinese families of children with EA.…”
Section: Introductionmentioning
confidence: 99%